OlsG (Sinac-1600) Is an ornithine lipid N-Methyltransferase from the planctomycete Singulisphaera acidiphila - Escobedo-Hinojosa, W.; Vences-Guzmán, M.; Schubotz, F.; Sandoval-Calderón, M.; Summons, Roger; López-Lara, I.; Geiger, O.; Sohlenkamp, C. (American Society for Biochemistry and Molecular Biology Inc., 2015)
Ornithine lipids (OLs) are phosphorus-free membrane lipids widespread in bacteria but absent from archaea and eukaryotes. In addition to the unmodified OLs, a variety of OL derivatives hydroxylated in different structural positions has been reported. Recently, methylated derivatives of OLs were described in several planctomycetes isolated from a peat bog in Northern Russia, although the gene/enzyme responsible for the N-methylation of OL remained obscure. Here we identify and characterize the OL N-methyltransferase OlsG (Sinac-1600) from the planctomycete Singulisphaera acidiphila. When OlsG is co-expressed with the OL synthase OlsF in Escherichia coli, methylated OL derivatives are formed. An in vitro characterization shows that OlsG is responsible for the 3-fold methylation of the terminal d-nitrogen of OL. Methylation is dependent on the presence of the detergent Triton X-100 and the methyldonor S-adenosylmethionine.